Contextualization of Mustahik fii Sabilillah at BAZNAS East Java Province - Abdul Wahab Naf'an (Management of Zakat and Waqf Journal (MAZAWA), 2023)
fii sabilillah is one of the criteria for mustahik zakat. In several regions in Indonesia, mustahik fii sabilillah is an active incidental mustahik and ranks third in priority mustahik. However, in the modern context, who is called fii sabilillah is ambiguous and has multiple interpretations. This is because fii sabillah contains a general meaning and changes the context of the past to the present. Therefore, this research seeks to reveal the contextual meaning of the definition of fii sabillah as applied at the BAZNAS East Java Province zakat institution, Sidoarjo, Indonesia. Apart from that, this research also reveals the relevance and analysis of ijtihadiyah used by these zakat institutions. Research data was explored qualitatively to produce in-depth data in a natural social setting. Apart from interviews, Data mining is complemented by documentation studies. Interviews were conducted with the Director, Distribution Division and several other officials at BAZNAS East Java Province. The findings are: From the results of the discussion above, two important things can be concluded in this research, ar: first, the contextualization of fii sabilillah as mustahik is categorized into three typologies; 1) typology of people who fight in the way of Allah to uphold the Islamic religion; 2) typology of people who spread Islam through da'wah; 3) typology of people who study religion and teach it. Second, analysis of contemporary interpretation shows that the contextualization carried out by BAZNAS East Java Province has similarities and relations to legal objectives. The fii sabilillah paradigm is given for the general benefit, not for individuals in need.